Extinct Lands, Temporal Geographies : Chicana Literature and the Urgency of Space - Brady, Mary Pat, 1961- (Book collections on Project MUSE., 2002)
Examines how Chicana literature -- its narrative techniques, stylistic conventions, plot dilemmas and resolutions -- interrogate the multiple ways space and social relations constitute each other.